Epigenetics and systems biology - Ringrose, Leonie (London Academic Press, 2017)
Epigenetics and Systems Biology highlights the need for collaboration between experiments and theoretical modeling that is required for successful application of systems biology in epigenetics studies. This book breaks down the obstacles which exist between systems biology and epigenetics researchers due to information barriers and segmented research, giving real-life examples of successful combinations of systems biology and epigenetics experiments. Each section covers one type of modeling and one set of epigenetic questions on which said models have been successfully applied. In addition, the book highlights how modeling and systems biology relate to studies of RNA, DNA, and genome instability, mechanisms of DNA damage signaling and repair, and the effect of the environment on genome stability.--Provided by publisher.
Computational identification of polycomb/trithorax response elements / Marc Rehmsmeier -- Modeling chromatin states / Marc Corrales and Guillaume J. Filion -- Crossing borders / Benjamin L. Moore and Colin A. Semple -- Inferring chromatin signaling from genome-wide ChIP-seq data / Juliane Perner and Ho-Ryun Chung -- "In vivo biochemistry" / Leonie Ringrose -- Modeling distributive histone modification by Dot1 methyltransferases / Dirk De Vos, Hanneke Vlaming, Barbara M. Bakker and Fred van Leeuwen -- Modeling bistable chromatin states / Ian B. Dodd and Kim Sneppen -- Quantitative environmentally triggered switching between stable epigenetic states / Rea Antoniou-Kourounioti and Martin Howard -- On the nature of chromatin 3d organization / Mario Nicodemi and Ana Pombo -- From chromosome conformation capture to polymer physics and back / Guido Tiana, Edith Heard and Luca Giorgetti -- A combination approach based on live-cell imaging and computational modeling to further our understanding of chromatin, epigenetics, and the genome / Kayo Hibino, Kazunari Kaizu, Koichi Takahashi and Kazuhiro Maeshima -- Capturing chromsome structural properties from their spatial and temporal fluctuations / Aurélien Bancaud, Olivier Gadal and Kerstin Bystricky.
Includes bibliographical references and index.
Keywords: Epigenetics; Systems biology; Electronic books